Politics of sickness: Political struggles over the meaning of “sick” in dealing with the COVID-19 pandemic in Indonesia - Adam Amin Bahar; Kacung Marijan; Antun Mardiyanta (Faculty of Social and Political Science, Universitas Airlangga, 2022)
In dealing with the COVID-19 pandemic, political actors in Indonesia tend to interpret “sick” in different ways. This study aims to discuss practices of political struggles over the meaning of “sick” in dealing with the COVID-19 pandemic in Indonesia. By using qualitative discourse analysis where data were mainly obtained from January to October 2020, this study found that political struggles over the meaning of “sick” in dealing with the COVID-19 pandemic in Indonesia were dominated by three major powers, namely the government, capitalist, and medical professionals. The meaning of “sick” given by these groups is not only different but also keeps changing from time to time, especially in certain political moments. This study found four important political moments which were closely related to the way these three groups of actors interpret the meaning of “sick” in the context of the COVID-19 pandemic. In one moment, “sick” was interpreted narrowly, while in another moment, “sick” was interpreted broadly. This study concludes that the struggle for the meaning of sick is an inherent practice in dealing with the COVID-19 pandemic in Indonesia. A further consequence is that the meaning of sick is not fixed as it is known so far but is more unfixed and contingent.